Nonlinear Utility Models Arising from Unmodelled Small World Intercorrelations - Bordley, Robert F.; Hazen, Gordon (Management Science, 1992)
Savage's axioms show the rationality of maximizing expected utility when all uncertainties are explicitly modelled. But individuals actually make decisions in bounded contexts called small worlds. Savage's axioms do not imply the optimality of maximizing expected utility in small worlds unless lotteries in different small worlds are probabilistically independent. Relaxing this independence assumption causes Savage's axioms to imply the optimality of maximizing a nonlinear utility model which includes, as special cases, the Chew weighted linear utility model, the Bell elation/disappointment model and the Allais mean/variance model in utility-independent small worlds.